Compreensão leitora nos anos iniciais: uma análise de pesquisas contemporâneas - Almeida, Maria Clara de (Universidade Federal de São Carlos, 2025)
Reading comprehension is a complex skill developed through social interactions, and it is fostered by dialogue and critical thinking, as indicated by Vygotsky (2001), Bakhtin (1997), and Solé (1998). This competence goes beyond the mere decoding of symbols, involving more elaborate linguistic and cognitive processes. In the early years of elementary education, its development can be enhanced through intentional teacher mediation, in contrast to traditional approaches based on memorization and repetition. This undergraduate thesis aims to analyze, through a qualitative and bibliographic approach, the contributions of contemporary research on reading comprehension in the early years of elementary school. Specifically, it seeks to: (1) investigate how recent studies conceive reading as a discursive and cognitive practice; (2) identify pedagogical strategies considered effective for developing reading competence; and (3) examine the role of teacher mediation and assessments in the meaning-making process. Sixteen scientific texts were analyzed and organized into three thematic categories. The results indicate that reading comprehension depends on the articulation of meaningful pedagogical practices, reading strategies at different stages (before, during, and after reading), and a teaching approach that considers language as social and interactive. It is concluded that teacher mediation is essential for creating conditions that promote reflective and critical reading, contributing to the formation of autonomous and participative readers.
Reading comprehension in elementary school: analysis of contemporary research
Keywords: Compreensão leitora; Anos iniciais; Estratégias de leitura; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM